Research progress of moxibustion in patients with chronic renal failure (艾灸在慢性肾功能衰竭患者中应用研究进展) - DENG Jianhua (邓建华); LI Mengya (李玉欣); WU Chunli (李梦雅); TIAN Chenchen (吴春丽); HU Fangfang (田晨晨) (中西医结合护理)
This paper summarized the literature of application of moxibustion therapy for patients with chronic renal failure. Moxibustion therapy is able to slowing the progression of renal function, improve the regulation of immune function, reduce the urinary protein. As a Traditional Chinese Medicine characteristic nursing technology, the moxibustion therapy shows advantages in slowing the progress of the renal failure. (本研究总结艾灸治疗慢性肾功能衰竭(CRF)的相关研究进展。艾灸可以改善CRF患者肾功能、调节患者免疫反应、减少尿蛋白和延缓肾功能进程, 艾灸的应用体现了中医护理的特色优势, 其在延缓肾功能衰竭进展方面具有积极的临床意义。)